APPLICATION OF PYROLYSIS REACTOR MODEL TECHNOLOGY BIOMASS RAW MATERIALS FOR MAKING CHARCOAL BRIQUETTES HOME INDUSTRY SCALE - Agustinus, Agustinus; Tambing, Enos; Payung Allo, Elisabeth; Lapituley, Frank; A. Wanaputra, Amadion (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The application of carbonization or carbonization model technology to reactor equipment uses a closed method. The purpose of using a closed system is to produce high quality carbon which is shiny black in nature and breaks easily when pressed with the thumb. This technological method is very practical for the community to apply both in the manufacture of reactors and the carbonization process to the manufacture of charcoal briquettes. The reactor can be made from used compressor cylinders or 12 kg gas cylinders. The material is then modified into a reactor device where combustion is carried out in the reactor tube. In the process of carbonizing biomass, neither agricultural nor industrial waste needs to wait until it turns into carbon, in this case black granules. In this training, participants were first provided with theory and explanations about the use of reactor tubes starting from the manufacturing process to carbon production. In making briquettes, several stages are carried out, including drying, waste sorting, carbonization, mixing with adhesive to printing with a briquette size of 3.18 cm and drying using an oven or sun. so that participants can practice at home. This training can provide skills to the participants, as well as open the mindset of how to use the waste around it to be used as a solid alternative fuel. It can also be used as a home industry business so that it can improve the household economy.